Optimization of insulation layer location and distribution considering maximum time lag and damping factor - Lu, Yihang; Hu, Jun; Zhong, Ke (Case studies in thermal engineering, 2022)
Approximately 35% of air conditioning energy consumption in buildings is caused by the heat transfer through the external walls, and this can be reduced by changing the location and distribution of insulation layers. To optimize the location and distribution of the insulation layers, transient heat conduction equation is solved by using the thermal quadrupole method, and a combinatorial algorithm is adopted to determine the wall structures. Time lag (TL) and damping factor (DF) are two evaluation indexes of wall thermal performance. The multi-objective algorithm is then adopted to determine the best wall configuration considering the maximum TL and DF. The external wall is composed of 20-cm thick reinforced concrete and 6-cm thick insulation layer, and the insulation layer is divided into one, two and three parts, respectively. The Pareto optimality shows that TL and DF of the wall with evenly distributed insulation layers are larger than that with unevenly distributed layers. For the same thickness of the insulation, both the DF and TL increase with increasing the number of the layers. The best performance is achieved when the three layers of insulation are placed on the outer surface, in the middle and 1 cm from the inner surface of the wall.